Factors Limiting Credit Uptake among the Youth in Kenya - Athiambo, Agnes (International Journal of Finance and Accounting, 2024)
Purpose: This study explores the factors limiting credit uptake among Kenyan youth, a demographic comprising about 75% of the country's population yet facing high unemployment and barriers in accessing credit to start businesses. Methodology: The study employed a qualitative design using semi-structured interviews with 20 Kenyan youth entrepreneurs (ages 18-35) who sought credit, and four focus groups with 6-8 diverse participants. Purposive sampling recruited participants who pursued credit within the past two years. Thematic analysis identified themes from the inductively coded interview and focus group data. Ethical protocols were followed. Validity and reliability were enhanced through triangulation, member checking, maintaining an audit trail, and strategies to minimize bias. Findings: The inadequate funding by easily accessible credit services such as the Hustler Fund is one of the notable impediments hindering the youth from starting small-scale business enterprises. Other barriers include stringent borrower age, business operational lifespan, and employability and minimum wage limit eligibility criteria. Unique Contribution to Theory, Practice and Policy: The study recommends government partnerships with private lenders, relaxed eligibility criteria for youth, credit guarantees or collateral support, expansion of low-risk credit products, and initiatives to build youth's banking histories. These recommendations integrate theoretical perspectives on financial literacy, social influences, and individual or systemic factors shaping credit behaviors. The study contributes to practice by proposing context-specific interventions tailored to Kenyan youth. Policy-wise, it aims to empower this valuable economic resource by improving credit access and harnessing their entrepreneurial potential.